Fizik öğretmen adaylarının yıldızlardan yıldızsızlara ünitesine ilişkin pedagojik alan bilgilerinin değerlendirilmesi - Unat, Onur (My University, 2011)
Anahtar Sözcükler: Pedagojik alan bilgisi, Yıldızlardan Yıldızsılara, Fizik Öğretmen Adayları ABSTRACT EVALUATION OF PRE-SERVICE PHYSICS TEACHERS’ PEDAGOGICAL CONTENT KNOWLEDGE REGARDING “FROM STARS TO QUASARS” UNIT Unat, Onur M.S., Physics Education Department Supervisor: Associated Professor Dr. Zeynep GÜREL October – 2011 The purpose of this research is to evaluate pre-service physics teachers’ pedagogical content knowledge regarding “From Stars to Quasars” unit within the scope of elements of pedagogical content knowledge. The sample of this study, in which case study research method was used, consisted of four pre-service physics teachers who were enrolled at Marmara University in the Physics Education Department senior class in 2010-2011. While choosing the participants, “Astronomy Subject Matter Test (ASMT)” was administered to 18 pre-service teachers to evaluate their subject matter knowledge level for astronomy. According to the test results, pre-service teachers having different knowledge levels were chosen to participate in this study to reveal different dimensions of the research problem. Data were collected via interviews and document analysis methods. The data from semi-structured interviews which were done in different times, Astronomy Subject Matter Test, lesson plans, and concept maps were analyzed by using the descriptive analysis. The findings of the study showed that pre-service physics teachers lacked of knowledge about “From Stars to Quasars” unit and had some misconceptions. The study also shows that there are some deficiencies in pre-service teachers’ pedagogical content knowledge and its sub-dimensions.
Keywords: Öğrenim ve Öğretim; Öğretmen Adayları